2020
DOI: 10.1177/0163443720972312
|View full text |Cite
|
Sign up to set email alerts
|

Hooking up with friends: LGBTQ+ young people, dating apps, friendship and safety

Abstract: Research exploring digital intimate publics tends to consider social media platforms and dating/hook-up apps separately, implying distance between social and sexual communication practices. This paper troubles that delineation by drawing on LGBTQ+ young people’s accounts of negotiating safety and risk in dating/hook-up apps, in which friendship practices are significant. We explore four key themes of friendship that arose in our analysis of interviews and workshop discussions: sharing mutuals (or friends-in-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 34 publications
5
22
0
Order By: Relevance
“…Despite their reputation as sex apps, hook-up apps afford making friends as well as communicating with existing friends (Byron et al 2021). Furthermore, our app-based encounters are often workshopped with friends, demonstrating that friendship is a guiding force in many queer lives (Byron et al 2021;Nardi 1999;Weeks et al 2001).…”
Section: Friendship -Paul Byronmentioning
confidence: 97%
See 3 more Smart Citations
“…Despite their reputation as sex apps, hook-up apps afford making friends as well as communicating with existing friends (Byron et al 2021). Furthermore, our app-based encounters are often workshopped with friends, demonstrating that friendship is a guiding force in many queer lives (Byron et al 2021;Nardi 1999;Weeks et al 2001).…”
Section: Friendship -Paul Byronmentioning
confidence: 97%
“…Despite their reputation as sex apps, hook-up apps afford making friends as well as communicating with existing friends (Byron et al 2021). Furthermore, our app-based encounters are often workshopped with friends, demonstrating that friendship is a guiding force in many queer lives (Byron et al 2021;Nardi 1999;Weeks et al 2001). As Race notes of hook-up app use: "sharing of captured images has emerged as a pleasurable activity and form of bonding among friends and acquain-tances in its own right, in activities informed by genres of gossip, boasting, archiving, memorabilia, humour, illustration, evidence, exposure and betrayal " (2015b, 504).…”
Section: Friendship -Paul Byronmentioning
confidence: 97%
See 2 more Smart Citations
“…Stereotypes about male sexuality (e.g., Snell et al, 1988 ) may also impact MSM’s consent practices, as research has shown that MSM feel pressured to engage in sexual activities, even when they feel ambivalent or uninterested (McKie, 2015 ; Sweeney, 2014 ; Beres et al, 2014 ). However, it is important to recall that many MSM enjoy receiving unsolicited DPs (Marcotte et al, 2020 ; Tziallas, 2015 ) and that MSM engage in a variety of socio-sexual interactions that blur the lines between platonic and sexual (Byron et al, 2021 ; Race, 2015 ). In the case of unsolicited DPs, MSM’s online interactions may complicate and obfuscate their consent practices, while also trivializing and perpetuating TFSV.…”
Section: Introductionmentioning
confidence: 99%